Fabrication and Experimental Study of Micro-gripper with Electrothermal Actuation by Stereolithography Method - Ülkir, Osman; Ertuğrul, İshak; Akkus, Nihat; Özer, Salih (Springer, 2022)
The aim of the study is to get high displacement values with low actuation voltage from the micro-gripper fabricated by stereolithography (SLA) method. Micro-grippers are devices based on a micro-electro-mechanical system (MEMS) preferred for manipulation and assembly in micro-fabrication. This article presents the modeling, fabrication, and experimental studies of a U-type electrothermal MEMS micro-gripper. The fabrication of the gripper was made by SLA, which is one of the additive manufacturing methods. The arm tip displacement of the gripper has been characterized in real-time by optical microscopy. In electrical characterization studies, the electrical voltage was applied to the pads of the micro-gripper. This voltage value was increased starting from 0V with 1V increments until deterioration was observed in the gripper. The micro-gripper is shown to actuate to a maximum opening displacement of 28.35 mu m at an applied voltage of 5V. The models are employed to examine key factors of the micro-gripper's performance including temperature distribution, displacement, and stresses based on an elastic analysis of structures. Experimental results for the displacement of the micro-gripper's arm tips were found to be in good agreement with the simulation results.
Keywords: additive manufacturing; electrothermal actuation; electrical characterization; MEMS; stereolithography; tip displacement; Piezoelectric Actuator; Design; Manipulation; Microgripper